Biomechanics of landing in gymnasts: a scoping review - Pavlasová, K.; Bizovská, L.; Gába, A.; Farana, R.; Janura, M. (Frontiers in Sports and Active Living, 2025)
This scoping review aimed to map methodologies used to assess landing biomechanics in gymnasts, focusing on muscle function and stability. Four research questions were formed, addressing common methodological approaches, factors affecting stability, and the relationships between muscle function, strength, and stability during landing. The searches were conducted across six databases and supplemented by reference and forward citation searches. Eight studies met the inclusion criteria, encompassing 212 participants aged 8-25 years, predominantly competitive gymnasts. The studies revealed significant variability in methods for assessing postural stabilization and muscle function during landing. Stabilization was evaluated using time to stabilization and center of pressure metrics, while muscle activity was predominantly measured via surface electromyography, focusing on lower limb muscles. Factors such as drop height, age, training level, and task-specific demands influenced muscle activity patterns but were inconsistently reported. Gymnasts demonstrated superior neuromuscular control compared to untrained individuals, with distinct muscle activation patterns during landing phases. Despite these insights, no studies examined the interplay between muscle strength, activity, and stabilization metrics. The lack of standardized methodologies limits direct comparisons and generalizations. This review highlights the need for consistent protocols and further research to explore relationships between muscle function, stability metrics, and performance outcomes in gymnastics.